A protein microarray for the rapid screening of patients suspected of infection with various food-borne helminthiases. - Jia-Xu Chen; Mu-Xin Chen; Lin Ai; Jun-Hu Chen; Shao-Hong Chen; Yong-Nian Zhang; Yu-Chun Cai; Xing-Quan Zhu; Xiao-Nong Zhou (Public Library of Science (PLoS), 2012)
BACKGROUND: Food-borne helminthiases (FBHs) have become increasingly important due to frequent occurrence and worldwide distribution. There is increasing demand for developing more sensitive, high-throughput techniques for the simultaneous detection of multiple parasitic diseases due to limitations in differential clinical diagnosis of FBHs with similar symptoms. These infections are difficult to diagnose correctly by conventional diagnostic approaches including serological approaches. METHODOLOGY/PRINCIPAL FINDINGS: In this study, antigens obtained from 5 parasite species, namely Cysticercus cellulosae, Angiostrongylus cantonensis, Paragonimus westermani, Trichinella spiralis and Spirometra sp., were semi-purified after immunoblotting. Sera from 365 human cases of helminthiasis and 80 healthy individuals were assayed with semi-purified antigens by both a protein microarray and the enzyme-linked immunosorbent assay (ELISA). The sensitivity, specificity and simplicity of each test for the end-user were evaluated. The specificity of the tests ranged from 97.0% (95% confidence interval (CI): 95.3-98.7%) to 100.0% (95% CI: 100.0%) in the protein microarray and from 97.7% (95% CI: 96.2-99.2%) to 100.0% (95% CI: 100.0%) in ELISA. The sensitivity varied from 85.7% (95% CI: 75.1-96.3%) to 92.1% (95% CI: 83.5-100.0%) in the protein microarray, while the corresponding values for ELISA were 82.0% (95% CI: 71.4-92.6%) to 92.1% (95% CI: 83.5-100.0%). Furthermore, the Youden index spanned from 0.83 to 0.92 in the protein microarray and from 0.80 to 0.92 in ELISA. For each parasite, the Youden index from the protein microarray was often slightly higher than the one from ELISA even though the same antigen was used. CONCLUSIONS/SIGNIFICANCE: The protein microarray platform is a convenient, versatile, high-throughput method that can easily be adapted to massive FBH screening.